A broadband circularly polarized slot antenna with a compact microstrip to CPW transition. Issue 5 (5th February 2018) - Guo, Jing‐Li; Zhou, Jun‐Na; Guan, Yu‐Bin; Sun, Bao‐Hua
Abstract: A simple structure of broadband circularly polarized slot antenna based on coplanar waveguide (CPW) feeding is proposed in this article. To obtain circular polarization with a single feed, a transition from microstrip to CPW is designed to excite the even and odd modes of the CPW simultaneously. By adjusting the relative position and dimensions of the two circular patches introduced at the end of microstrip line and CPW, a 90° phase difference between two modes can be produced. When the two modes are coupled into the wide slot antenna, broadband circular polarization operation can be realized. The 10‐dB reflection coefficient bandwidth of the proposed antenna is 88.2% (2.49‐6.42 GHz) and 3‐dB AR bandwidth attains 50% (2.72‐4.49 GHz).